Consumption of alcoholic beverages and tobacco among students of the Dentistry course of the University Center of Patos De Minas – UNIPAM (Research, Society and Development, 2021)
This study aimed to evaluate the consumption of alcoholic beverages and tobacco among students of the Dentistry course at the University Center of Patos de Minas – UNIPAM. This is an observational, cross-sectional interference study, with an intentional non-probabilistic sample. The questionnaire was applied to 165 students, 40 males and 125 females with an average age of 21.45 years. The data revealed a low prevalence of alcohol consumption among the participants, around 22% of the students had never drank. Among those who consumed alcohol, most consumed it 2 to 4 times a week, in the last 12 months they did not experience an episode of not being able to stop drinking, did not consume alcohol in the morning, never lost any function, no had alcoholic amnesia, did not cause harm to third parties due to the use of alcoholic beverages. A minority consumes 5 or more doses of alcoholic beverages on a single occasion and confirms feeling guilty or remorseful for drinking alcoholic beverages in the last 12 months. Most students have never smoked a cigarette. Among the minority who smoke, the majority reveals having been influenced by colleagues, claims to have used cigarettes on the university premises, and, in the last month, even used tobacco for chewing, snuff, hookah pipe, cigars and pipes. No statistical difference regarding alcohol and tobacco consumption was noticed between the different periods of the evaluated Dentistry courses.